2015
DOI: 10.4067/s0718-221x2015005000071
|View full text |Cite
|
Sign up to set email alerts
|

The effect of traditional hygro-thermal pretreatments on the acoustical characteristics of white mulberry wood (Morus alba)

Abstract: The wood used in making musical instruments usually undergoes pre-treatments or conditioning. Some processes have resulted from laboratory research, while many treatments are applied by craftsmen using traditional methods that have not yet been scientifically assessed. This paper is based on laboratory methods which simulate hydrothermal pre-treatments traditionally applied by Iranian lute makers to mulberry (Morus alba), an important wood for lutes from the Middle East to Japan. By applying a cyclic process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…Another hypothesis would be that, as Morus is a ring porous species (Karami et al 2010), a very light wood as the one studied here would include a high proportion of vessels and parenchyma compared to that of fibres. This is consistent with previous observations that mulberry specimens with narrower rings (i.e., for this ring-porous wood, with wider proportion of vessel-rich earlywood and small proportion of fiber-rich latewood) tend to have lower values of both γ and E' L /γ (Se Golpayegani et al 2015). Across several studies (present results, Roohnia 2005, Se Golpayegani et al 2012, 2015 there is a positive correlation between γ and E' L /γ, although E' L /γ is theoretically determined at cell-wall scale and thus is generally little dependent of specific gravity (Norimoto et al 1986).…”
Section: Properties Of Untreated Mulberry Woodsupporting
confidence: 93%
See 4 more Smart Citations
“…Another hypothesis would be that, as Morus is a ring porous species (Karami et al 2010), a very light wood as the one studied here would include a high proportion of vessels and parenchyma compared to that of fibres. This is consistent with previous observations that mulberry specimens with narrower rings (i.e., for this ring-porous wood, with wider proportion of vessel-rich earlywood and small proportion of fiber-rich latewood) tend to have lower values of both γ and E' L /γ (Se Golpayegani et al 2015). Across several studies (present results, Roohnia 2005, Se Golpayegani et al 2012, 2015 there is a positive correlation between γ and E' L /γ, although E' L /γ is theoretically determined at cell-wall scale and thus is generally little dependent of specific gravity (Norimoto et al 1986).…”
Section: Properties Of Untreated Mulberry Woodsupporting
confidence: 93%
“…The studied material of white mulberry wood had a specific gravity (γ) of 0.49 on average (from 0.43 to 0.53) and an equilibrium moisture content at 20 °C and 65%RH (EMC) of 9.3 ± 0.4%. These values can be compared to previously published studies by Se Golpayegani et al (2012Golpayegani et al ( , 2015, who reported a significantly higher γ of 0.54 on average (from 0.45 to 0.60) and a slightly lower EMC of 8.0%. The wood used in the present study had narrower growth ring and consequently lower late wood percentage, which can explain the difference considering the ring-porous nature of this species.…”
Section: Properties Of Untreated Mulberry Woodsupporting
confidence: 64%
See 3 more Smart Citations